THE CASES OF STUDENT BURNOUT AT INDEPENDENT - Nadjibah Yahya; Andri Nirwana; G Giyoto; Setyo Dwi Raharjo (Profetika: Jurnal Studi Islam, 2022)
This study aims to find out how big burnout cases are in independent medical practice. It was taken from burnout cases that occurred in independent medical practices, from January 2018 to December 2021. The patient was tested for burnout with Maslach Burnout Inventory-Human Service Survey (MBI-HSS) instrument. Burnout cases that enter the independent doctor’s practice are those with physical symptoms such as stomach complaints and heart complaints. The method used in this research is quantitative and qualitative. Qualitative to see the relationship between sex and burnout shirts. Qualitative to analyze suggested solutions. The results obtained are as follows, there is an almost threefold increase in burnout cases during the pandemic. Calculation of chi-squared shows that gender affects burnout cases in students seen in the chi quadrant with an error rate of 5%. Before the pandemic, the incidence of burnout in women was more. After the pandemic, there were more burnout cases in men. The solution that should be done is to create a special curriculum on professional development to explore the motivation of students to overcome burnout. Some examples of countermeasures are those that have been implemented at the Faculty of Medicine, Universitas Indonesia, Indonesia, or do a coping strategy. This research is done to know how to prevent cases burnout cases in more students